Trust comprehensive evaluation based on the fuzzy inference theory in P2P network - QUAN Yi-ning 1; HU Yu-pu 1; LI Xin-she1 (Tongxin xuebao)
Aimed at characteristic of ambiguous relationship among entities in P2P network, as foundation of fuzzy inference theory, a fuzzy proposition deduction system was given, also a trust recommendation and comprehensive evaluation model in P2P network based on triple I fuzzy inference algorithm was built. In this model, fuzzy reasoning was on the basis of multiple recommendation rules ,it had achieved the comprehensive evaluation of recommendation trust, established a new trust model in P2P network environment. The results of simulation experiment show that this model can increase the success rate of transaction greatly, and make it possible to establish trust relationship between peers more ef-fectively.